Hubungan Antara Konsep Diri dan Dukungan Keluarga terhadap Tingkat Depresi pada Pasien Pasca Stoke - Dea Putri Fadila; Anggie Stiexs; Budi Antoro (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Post-stroke depression is a common psychological complication among stroke survivors. Stroke is a leading cause of deat h and disability and can cause physical and psychological impacts, including depression. Changes in physical condition after a stroke can affect a patient's self-concept, while family support plays a crucial role in the process of adaptation and psychological recovery. This study aims to determine the relationship between self-concept and family support with levels of depression in post-stroke patients at Dr. A. Dadi Tjokrodipo Regional Hospital in 2025. This study used a quantitative correlational analytic design with a cross-sectional approach. The study population consisted of 267 respondents, with a sample size of 73 respondents determined using the Slovin formula with a purposive sampling technique. The research instruments used included a 25-question self-concept questionnaire, a 15-question family support questionnaire, and a 15-question Geriatric Depression Scale (GDS-15) questionnaire to measure the level of depression in respondents. Data analysis used univariate and bivariate analysis with the chi-square test. The results showed a relationship between self-concept and depression levels with a p-value of 0.000 (p<0.05), and a relationship between family support and depression levels with a p-value of 0.034 (p<0.05). Most respondents had a negative self-concept (63.0%), of 29 respondents, the majority had moderate family support (39.7%), and the majority of 35 respondents experienced moderate depression (47.9%). It is recommended that healthcare professionals provide education and support to post-stroke patients and their families regarding the importance of strengthening self-concept and family support to reduce depression levels in post-stroke patients.